Peptide Tat(48–60) YVEEL protects against necrotizing enterocolitis through inhibition of toll-like receptor 4-mediated signaling in a phosphatidylinositol 3-kinase/AKT dependent manner - Yan, Xiangyun; Cao, Yan; Chen, Wenjuan; Yu, Qinlei; Chen, Yanjie; Yao, Shuwen; Jiang, Chengyao; Chen, Xiaohui; Han, Shuping (Frontiers in Nutrition, 2022)
Necrotizing enterocolitis (NEC) is a catastrophic disease largely occurring in preterm infants, and toll-like receptor 4 (TLR4) has been implicated in its pathogenesis. The current therapeutic strategies for NEC are, however, far from optimal. In the present study, a whey-derived antioxidative peptide conjugated with a cell-penetrating TAT [Tat (48–60) YVEEL] was prepared to endow it with enhanced cell uptake capability and bioavailability. The protective effect of Tat (48–60) YVEEL on experimental NEC was evaluated both in vitro and in vivo. Inhibition of TLR4-mediated signaling by Tat (48–60) YVEEL was assessed in FHC and IEC-6 enterocytes, neonatal rat model of NEC, and the mechanism underlying this effect was determined. Tat (48–60) YVEEL significantly inhibited TLR4-mediated expression of pro-inflammatory cytokines, p65 nuclear translocation and restored the impaired enterocyte migration in cultured enterocytes. In addition, Tat (48–60) YVEEL administration strikingly increased the survival rate, and reduced the severity of NEC in rats through inhibition of TLR4-mediated signaling. These protective effects of Tat (48–60) YVEEL occurred in a PI3K/AKT dependent manner, as administration of PI3K activator Ys49 abrogated its protective effects. Combined with liposomes, Tat (48–60) YVEEL demonstrated longer retention in the intestines that better for potential clinical applications. These data demonstrate that Tat (48–60) YVEEL protects against NEC through inhibition of TLR4-mediated signaling in a PI3K/AKT dependent manner, and offer a potential therapeutic approach to this disease.